Mitologi Sedekah: Penerapan Semiotika Roland Barthes pada Q.S. Al-Baqarah [2]: 271 - Habibie, Ilham Akbar; Hairul, Moh. Azwar (Al-Qudwah, 2023)
This research discusses the meaning of charity in interpreting Surah Al-Baqarah [2]: 271 using Roland Barthes' semiotic approach. The article focuses on revealing both denotative and connotative meanings, as well as discussing the signs found in Surah Al-Baqarah [2]: 271. The method employed in this research is qualitative, utilizing primary and secondary source analysis. Primary sources include classical and contemporary interpretations and Roland Barthes' book titled "Mythologies." Classical interpretations refer to Al-Maraghi's, Marah Labid's, and Jalalain's interpretations, while contemporary interpretations refer to Al-Mishbah's interpretation discussing Surah Al-Baqarah [2]: 271. Secondary data include articles and books discussing the concept of charity, which are works of others but are still relevant to the interpretation of charity. The study concludes that there are denotative and connotative meanings in Surah Al-Baqarah [2]: 271 related to charity. The denotative meaning of Surah Al-Baqarah [2]: 271 is giving wealth to others based on alleviating the burden of those in need with the intention of drawing closer to Allah. Meanwhile, its connotative meaning includes doing good deeds, speaking kind words, uttering greetings, commanding good deeds, and forbidding wrongdoing. The mythological meaning of Surah Al-Baqarah [2]: 271 is derived from the most dominant connotative meaning, which encompasses the prohibition of wrongdoing to oneself and others. The significance of the meaning of Surah Al-Baqarah [2]: 271 in the contemporary context is manifested in organizations such as the United Nations (UN). The UN is an organization tasked with maintaining communication with other countries, preserving national security stability, ensuring economic stability, and safeguarding human rights stability.   Abstrak: Penelitian ini membahas makna sedekah dalam penafsiran Q.S. Al-Baqarah [2]: 271 dengan menggunakan pendekatan semiotika Roland Barthes. Artikel ini berfokus untuk mengungkapkan makna denotatif dan konotatif, serta mendiskusikan tentang tanda yang terdapat dalam Q.S. Al-Baqarah [2]: 271. Metode dalam penelitian ini adalah kualitatif dengan analisis sumber primer dan sekunder. Sumber primer berasal dari tafsir klasik, kontemporer, dan buku karya Roland Barthes. Adapun tafsir klasik dalam penelitian ini merujuk pada tafsir Al-Maraghi, tafsir Marah Labid, tafsir Jalalain, sedangkan tafsir kontemporer merujuk pada tafsir Al-Mishbah yang membahas Q.S. Al-Baqarah [2]: 271, adapun buku Barthes berjudul “mythologies”. Data sekunder adalah artikel dan buku yang membahas konsep sedekah dan merupakan karya orang lain namun masih bersinggungan dengan hasil penafsiran sedekah. Penelitian ini menyimpulkan bahwa terdapat makna denotatif dan konotatif dalam Q.S. Al-Baqarah [2]: 271 yang berkaitan dengan sedekah. Makna denotatif Q.S. Al-Baqarah [2]: 271 adalah memberikan harta kepada orang lain atas dasar meringankan beban orang yang membutuhkan dengan niat mendekatkan diri kepada Allah. Sedangkan makna konotatifnya adalah berbuat baik, perkataan baik, mengucapkan salam, perintah melakukan perbuatan baik, dan larangan barbuat zalim. Adapun makna mitologi dari Q.S. Al-Baqarah [2]: 271 didapatkan dari makna konotatif yang paling dominan dan mencakup, yakni larangan berbuat zalim pada diri sendiri maupun orang lain. Signifikansi makna dari Q.S. Al-Baqarah [2]: 271 pada konteks kekinian terwujud dalam organisasi seperti “Perserikatan Bangsa-bangsa (PBB). PBB adalah organisasi yang bertugas untuk menjaga hubungan komunikasi dengan negara lain, menjaga stabilitas keamanan negara, menjaga stabilitas ekonomi, dan menjaga stabilitas hak asasi manusia.